If I had a million - Andrews, Robert Hardy 1903-1976 (KL studio classics, 2023)
"To prevent his inheritance from going to his greedy family, a dying steel tycoon chooses eight random strangers and gives them each one million bucks. Among those chosen is an entertainer who uses the money to clear bad drivers from the road, a Marine who believes the check is an April Fool's Day prank, and an office clerk who finally sees an opportunity to quit his job." [Container]